Multi-instrument analysis of medium-scale travelling ionospheric disturbances generated by an intense tropospheric jet-front system with severe convection in Europe in August 2023 - Barta Veronika; Potuznikova Katerina; Knížová Petra Koucká; Chum Jaroslav; Mielich Jens; Guerra Marco; Buresova Dalia; Sivakandan Mani; Verhulst Tobias G. W.; Berényi Kitti A.; Altadill David; Segarra Antoni; et al. (Journal of Space Weather and Space Climate, 2025)
Tropospheric jet-front systems and intense convection are known to be potential sources of atmospheric gravity waves (AGWs), which can propagate upward. When AGWs reach the height of the coupled thermosphere-ionosphere system, they interact with the ionised medium and cause wave-like oscillations known as travelling ionospheric disturbances (TIDs). The main purpose of the present study is to investigate medium-scale TID (MSTID) activity during the passage of a jet-front system using different observational techniques, namely: vertical ionospheric soundings at seven European ionosonde stations, Continuous Doppler Sounding System (CDSS) in Czech Republic, oblique Digisonde-to-Digisonde (D2D) sounding, and Total Electron Content (TEC) measurements provided by ground-based Global Navigation Satellite System (GNSS) receivers co-located with the ionosondes. A strong jet-front system accompanied by intense convection passed through continental Europe between 25 and 29 August 2023. The severe convection and the unusually persistent meridional jet stream caused a strong vertical wind shear across the entire troposphere, which was favourable to the generation of atmospheric gravity waves. During the event, the geomagnetic activity can be considered calm. The most intense MSTID activity was observed in ionograms, in the single station detrended TEC (dTEC) measurements, and also in the CDSS Doppler shift records during the daytime (~06–13 UT) on 27 August, when the jet stream reached its highest velocities (~200 km/h) over continental Europe. Signatures of MSTIDs were also observed during other analysed time periods of the event. Based on the ionospheric and meteorological observations, the location and time of these enhanced TID activities coincided with local thunderstorms and a Mesoscale Convective System (MCS) event. According to the records, the dominant periods of the disturbances varied between 15 and 70 min. When summarizing, our multi-instrumental observations confirmed that jet-front systems accompanied by severe tropospheric convection could be significant sources of AGWs, which reach the ionosphere and trigger MSTIDs.